Roger A. Pryor correspondence - Pryor, Roger A. (Roger Atkinson), 1828-1919.
Letter (1867 October 5; New York, N.Y.) written by Pryor for publication in the Whig (Weekly Richmond Whig, Richmond, Va.) in which he advocated reconciliation between North and South to ensure peace and prosperity following the Civil War.
Typewritten transcript.
Editor and lawyer, of Petersburg and Richmond, Va.; U.S. representative from Virginia; U.S. minister to Greece; and Confederate Army officer. In 1866, Pryor moved to New York, N.Y., where he practiced law and later served on the New York Supreme Court.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Weekly Richmond Whig (Richmond, Va. : 1867); Reconstruction (U.S. history, 1865-1877); Southern States -- History -- 1865-1877.; United States -- Politics and government -- 1865-1877.; Army officers, Confederate; Editors; Jurists; Lawyers; Representatives, U.S. Congress -- Virginia